Development and Psychometric Evaluation of Coronary Artery Disease Treatment Adherence Scale - Nahid Dehghan Nayeri; Mohammad Ali Yadegary; Khatereh Seylani; Elham Navab (Cardiology and Therapy, 2019)
Abstract Introduction Poor treatment adherence reduces treatment effectiveness and increases healthcare costs. The promotion of treatment adherence necessitates valid and reliable tools to assess the effectiveness of adherence promotion strategies. This study was undertaken to develop and evaluate the psychometric properties of the Coronary Artery Disease Treatment Adherence Scale. Methods This methodological study was conducted in two phases. In the first phase, a literature review was done and a 62-item scale was developed. In the second phase, different methods were used to assess the psychometric properties of the scale, namely its face validity, content validity, construct validity, internal consistency, and test–retest stability. Results During face and content validity assessments, the number of items was reduced from 62 to 53. Moreover, in construct validity assessment via exploratory factor analysis, 18 items were deleted because their factor loading values were less than 0.3. The remaining 35 items were loaded on four factors, namely medication adherence, dietary adherence, exercise adherence, and healthy lifestyle adherence. The Cronbach’s alpha values of the scale before and after factor analysis were 0.850 and 0.862, respectively. Its test–retest intraclass correlation coefficient was also 0.85. Conclusions The Coronary Artery Disease Treatment Adherence Scale is a valid and reliable tool and can be used in different healthcare settings for the assessment of treatment adherence among patients’ with coronary artery disease. Trial Registration Tehran University of Medical Sciences, identifier, 35456.